O significado do trabalho para juízes estaduais - Silva, Ricardo Augusto Ferreira e (2017)
Work has been seen not only as a source of income for subsistence, but as means for the individual to relate to others and to feel as part of society. This research aims to describe the meaning of the work of the judge, relying on the dimensions of meaning described in the model MOW ‒ Meaning of Work (1987): (a) centrality, (b) social norms and (c) objectives and results valued at work. The research carried out at the Court of Justice of the State of Goiás, covered the 13 judicial regions. Data collection took place between October and December 2016; 20 first-degree judges were interviewed through a semi-structured script. The data obtained from the answers to the questions were analyzed through textual data techniques and, later, by content analysis. The results of the research showed that there was no consensus regarding the centrality of work in relation to time and in comparison to work with other spheres of life, although most interviewees affirmed that the Family is a priority, followed by work and religion. The concept of meaning of work, in a unanimous way, is associated with something useful and productive to society. In this sense, judges consider work more as a duty than a right before society. The interviewees demonstrated incisive behaviour in the question of the CNJ and the superior courts being organs of a political character, for having at the top members not coming from the judiciary. The way of legislating through resolutions is another criticized topic, which directly interferes with the autonomy and independence of the judges. Although feelings of frustration and happiness are counterbalanced among magistrates, research data converge with the positive conception pattern where work has been seen as value-creating activity in society.